2016
DOI: 10.1007/s10340-016-0745-8
|View full text |Cite
|
Sign up to set email alerts
|

Are wild flowers and insect honeydews potential food resources for adults of the olive moth, Prays oleae?

Abstract: The use of non-crop resources by natural enemies and their potentialities to enhance their effectiveness as pest control agents is increasing as a method for conservation biological control. Nevertheless, the effect of consumption of non-crop resources by pests has been generally overlooked being this knowledge crucial to favor natural enemies but not pests. In the present work, insect honeydews and flowers suitability as food resources for the olive tree key-pest Prays oleae were analyzed under laboratory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
25
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 49 publications
6
25
0
1
Order By: Relevance
“…To our knowledge, this is the first study that demonstrates that a honeydew type is a superior source for parasitoids when compared to nectar or the positive control (honey at 10% herein). Two other works support our results and, moreover, suggest that not only S. oleae parasitoids can benefit from this rich honeydew but also parasitoids of other olive pests as well as the own olive pests (Wang et al 2011, Villa et al 2016. Wang et al (2011), found that S.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To our knowledge, this is the first study that demonstrates that a honeydew type is a superior source for parasitoids when compared to nectar or the positive control (honey at 10% herein). Two other works support our results and, moreover, suggest that not only S. oleae parasitoids can benefit from this rich honeydew but also parasitoids of other olive pests as well as the own olive pests (Wang et al 2011, Villa et al 2016. Wang et al (2011), found that S.…”
Section: Discussionsupporting
confidence: 91%
“…Braconidae) as the positive control. Villa et al (2016) found that the olive moth Prays oleae Bernard (Lepidopteta: Praydidae) reaches the highest survival when fed on this honeydew compared with other honeydew and flowers. These latter results are in concordance with Wäckers et al (2008) and , which showed that parasitoids of non-honeydew-producing insects can also benefit from honeydew.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Further studies should also address the nutritional composition of the most abundant pollen types found in C. carnea guts. Finally, few studies have addressed the effect of olive grove agroecosystem vegetation on olive tree pests (Villa et al, 2016c). Further studies should address how changes in flowering plant biodiversity affect pest control accomplished by C. carnea.…”
Section: Resultsmentioning
confidence: 99%